Membangun Keterampilan Berpikir Kritis Siswa Melalui Literasi Digital Berbasis STEM pada Masa Pandemik Covid 19 - Fitri Handayani (CENDEKIAWAN, 2020)
During the Covid 19 pandemic, learning allowed children to think critically and creatively through online learning based on STEM (Science, Technology, Engineering, Mathematics). STEM is developed integrated with the implementation of 2013 curriculum learning that leads to the development of 21st-century learning. STEM-based digital literacy is learning that has a syntax to build students' skills in solving problems and critical thinking skills (Critical Thinking Skills) so that they can actively build knowledge through digital literacy STEM-based. STEM as a learning approach as a bridge in the development of science to improve students' critical thinking skills (Critical Thinking Skill). This research is a qualitative research which is library research using books and other literature as the main object. The expected results by improving STEM-based online critical thinking skills for teachers are to provide changes in the pattern of learning activities and increase the content of new STEM-based science, especially during the Covid 19 pandemic, which can provide more space for teachers to explore student skills from afar with STAM-based digital literacy. The result of science education from STEM-based digital literacy that is expected for students is that students can learn and be skilled to improve critical thinking skills through STEM-based Digital Literacy, which in turn can be skilled in solving problems in real life.